MEASUREMENT OF DEFORMATION OF BUILDINGS AND STRUCTURES BY GEODETIC METHODS - Akhmedov Bakhriddin Madaminovich (Western European Studies, 2024)
This article highlights information about the measurement of deformation of buildings and structures by geodetic methods, calculation tasks using a certain type of alignment in the study of precipitation
Keywords: geodetic instruments; leveling nets